2009
DOI: 10.1111/j.1749-6632.2008.03628.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xenoestrogens on the Differentiation of Behaviorally Relevant Neural Circuits in Higher Vertebrates

Abstract: Several environmental chemicals have the capability of impacting endocrine function (endocrine disrupting chemicals [EDCs]), and therefore they may have long-term consequences, especially if exposure occurs during embryonic development. In this study we present data relative to two widely used animal models: the Japanese quail and the mouse. These two species have been used to understand neural, neuroendocrine, and behavioral components of reproduction and are optimal models to understand how these components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…However, BPA when injected to immature male in the present study showed more activity in reducing circulatory testosterone levels and sexual behavior than in ova injection. Consequently, the permanent effects of the estrogen like compounds on sexual behavioral can be induced by administering during a sensitive developmental stage, such as the period of differentiation or maturation of the reproductive organs (Panzica et al, 2009). Whereas estrogen-induced morphological changes in the testis have been reported to disappear after hatching (Halldin et al, 1999(Halldin et al, , 2003 while the estrogen-induced effects on the male brain are rather permanent.…”
Section: Discussionmentioning
confidence: 99%
“…However, BPA when injected to immature male in the present study showed more activity in reducing circulatory testosterone levels and sexual behavior than in ova injection. Consequently, the permanent effects of the estrogen like compounds on sexual behavioral can be induced by administering during a sensitive developmental stage, such as the period of differentiation or maturation of the reproductive organs (Panzica et al, 2009). Whereas estrogen-induced morphological changes in the testis have been reported to disappear after hatching (Halldin et al, 1999(Halldin et al, , 2003 while the estrogen-induced effects on the male brain are rather permanent.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some studies have demonstrated that MDCs can masculinize or feminize energy balancing traits depending upon type and dose of the tested chemical, the timing of exposure and the metabolic challenge. In experimental animals, sex-dependent differences in body weight in response to prenatal or early postnatal exposure to low doses of BPA or DES have been reported; both chemicals increased body weight in female rodents but decreased or did not affect it in males [328, 443]. A recent study has examined in detail the energy balance traits of mice prenatally exposed either to a low or a high dose of BPA or to DES showing that exposure to BPA but not to DES hypermasculinized male and masculinized female mice (see also [440]).…”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…Nearly all Kiss1 neurons in the RP3V and ARC co-express ERα, and a subset of RP3V Kiss1 neurons co-express ERβ (Smith et al, 2005, Smith et al, 2006) suggesting that disruption of ER expression within this neuronal phenotype could affect its sex specific ontogeny and function. Gestational and/or postnatal BPA exposure has been shown to alter Kiss1 mRNA expression within whole hypothalamic micropunches (Navarro et al, 2009, Xi et al, 2010), and RP3V Kiss1-immunoreactivity (Bai et al, 2011, Panzica et al, 2009) during peripuberty and adulthood. Although RP3V Kiss1 expression is not apparent in either sex until approximately the second week of life (Cao and Patisaul, 2011, Clarkson et al, 2009) we have shown that neonatal exposure to estrogen or an ERα selective agonist (Bateman and Patisaul, 2008, Patisaul, Todd, 2009) can defeminize kisspeptin signaling pathways in the adult RP3V, suggesting that the first few days of life may be a critical window of BPA vulnerability, and that this disruption may be apparent prior to puberty.…”
Section: Introductionmentioning
confidence: 99%